On Multiple Metonymies within Indirect Speech Acts - Kosecki, Krzysztof (Research in Language, 2007)
Indirect speech acts are frequently structured by more than a single metonymy. The metonymies are related not only to the illocutionary force of the utterances, but also function within the individual lexemes being their parts. An indirect speech act can thus involve not only multiple, but also multi-levelled operation of conceptual metonymy.